واقع الإتصال الديني في المؤسسات المسجدية مسجد السلام بالمسيلة نموذجا - بوصلاح, بلال (كلية العلوم الانسانية والاجتماعية جامعة محمد بوضياف بالمسيلة, 2018)
لقدتناولت دراستناموضوع واقع الإتصال الديني في المؤسسات المسجدية من اجل التعرف على طبيعة واقع الإتصال المعاش ومدى مناسبته لمجتمعنا العربي والإسلامي، تمحورت إشكاليتها حول : • ما واقع الإتصال الديني في المؤسسات المسجدية؟ وإستخدمنا في هذه الدراسة منهج دراسة حالة المنهج المسحي وإعتمدنا على العينة فطبقنا منها العينة القصدية وقسمت الدراسة إلى فصلين : الفصل الأول المتعلق بالإطار المنهجي للدراسة ،أماالفصل الثاني خصص للإطار التطبيقي للدراسة وذلك حتىيتسنى لنا الإلمام بمختلف الأفكارالقيمة سواء السلبية أو الإيجابية الواردة فيه. ومن أهم النتائجالتي توصنا إليها في هذه الدراسة,أن واقع الإتصال الديني في المؤسسات المسجدية, دور مهم وبارز في قيام المؤسسة. Abstract : Our study dealt with the reality of religious communication in the mosque institutions in order to identify the nature of the reality of the pension and its suitability to our Arab and Islamic society. The problem centered on: • What is the reality of religious communication in mosques? In this study, we used the case study method of the survey method and relied on the sample The study was divided into two chapters: The first chapter deals with the methodological framework of the study, while the second chapter is devoted to the applied framework of the study So that we can know the various ideas valuable, whether negative or positive contained therein. One of the most important findings that we have mentioned in this study is that the reality of religious communication in mosques is an important and prominent role in the establishment of the institution.
Keywords: الإتصال الديني - المؤسسات المسجدية